Quality by design approach for the formulation of bilayer tablets of domperidone and itopride in gastro-esophageal reflux disease - Roshani Prajapati, Bhavna Kumar, Jagannath Sahoo, Shailendra Shakya, Diwya Kumar Lal (Journal of Applied Pharmaceutical Science, 2024)
In the current work, a bilayer tablet of itopride gastroretentive and domperidone immediate release formulation was developed showing the synergistic effect of gastric motility in gastroesophageal reflux disease, through antidopaminergic and antiacetylcholine stearic activities. A bilayer tablet of domperidone and itopride was optimized using quality by design and its product performance was analyzed. Itopride was designed to be gastroretentive and remains in the stomach for a longer period, providing sustained release. The domperidone layer was optimized by an empirical hit and trial method, while the itopride layer was optimized using the Box Behnken experimental design. Three independent variables were considered as hydroxypropyl methyl cellulose K 100 M, xanthum gum, and Carbomer 974 with dependent variables like floating lag time, swellable index, and percentage drug release at 24 hours. Quality target product profile and critical quality attributes were studied which helps in an effective way to develop bilayer tablets. The excipients were chosen based on the time taken by medicaments to be released and the quantity was optimized according to Handbook of Pharmaceutical Excipient. From the optimization processes, DF5 and IH2 were selected as optimized composition for the formulation of domperidone and itopride layer of bilayer tablet respectively. The bilayer tablets were formulated in 16 × 8.26 mm oblong plain biconcave die and punch. The in-vitro drug release of domperidone was 99.39% in 30 minutes and itopride was 27.50%, 53.45%, and 93.65% at 4, 16, and 24 hours respectively.
Keywords: Quality by design, bilayer tablets, immediate release, gastro-retentive, quality control